Guillaume Jullian de la Fuente: la idea fundamental del diseño de Le Corbusier - Shah, Mahnaz (Dearq, 2014)
Guillaume Jullian de la Fuente (1931-2008) was Le Corbusier’s (1887 - 1965) primary assistant in many of his later projects. I first became acquainted with Jullian in 2007 at MIT, when Stanford Anderson very kindly introduced me to Ann Pendleton-Jullian and through her I met Jullian. My brief correspondence and discussions with him led me to be introduced to a facet of Le Corbusier work that remains largely unexplored, and which Jullian termed the ‘Potato Building typology’. This paper is an attempt to briefly present the ‘horizontal’ element in Le Corbusier’s oeuvre and its significance in determining the parameters of this proposed typology.